Virtual Learning Stress: Addressing Anxiety In EFL Adult Learners at Indonesian Private Universities - Sholeh, Agus; Muchibuddin, Muchibuddin (Journal of Languages and Language Teaching, 2025)
The increasing reliance on virtual learning in higher education has supported the development of flexible and accessible learning environments, yet it may also heighten anxiety among students, particularly those studying English as a Foreign Language (EFL). Although virtual learning tools offer significant advantages, research on their psychological impact remains limited, highlighting a gap between technological advancements and understanding of their effects on student well-being. This study examines the relationship between virtual learning and student anxiety, exploring the strategies students use to manage this challenge. Employing a descriptive qualitative approach, data were collected through questionnaires and interviews with 22 English-major undergraduates. Findings indicate that students often experience anxiety due to technological distractions and comprehension difficulties in virtual classrooms. However, students mitigate this anxiety by adopting positive thinking and engaging in relaxing activities. These insights underscore the need for supportive virtual learning environments that prioritize students' emotional well-being alongside academic outcomes.